What is the right cash conversion cycle for your supply chain?. (1st January 2011) - Grosse-Ruyken, Pan Theo; Wagner, Stephan M.; Jönke, Ruben
Supply chain finance is undergoing a transformation. Supply chains are often so tightly coupled that the domino effect of suboptimal working capital management can lead to financial glitches at a single supplier and even bankruptcy. Thus, each working capital management decision should consider every upstream and downstream partner within the supply chain. The cash conversion cycle (CCC) is therefore an excellent measure of a firm's performance. Results indicate a significant negative relationship between the CCC and return on capital employed (ROCE). We argue that the optimal level of CCC for responsive supply chains must be assessed holistically, and conclude that the right working capital management depends on the business model, its specific supply chain design configurations, and risk aspects within the supply chain.